Is peer-to-peer electricity trading empowering users? Evidence on motivations and roles in a prosumer business model trial in Australia - Wilkinson, Sam; Hojckova, K.; Campbell, Christine; Morrison, Greg; Sandén, B. (2020)
© 2020 Elsevier Ltd